A model to explain the angular distribution of and decay into and. (February 2019) - Alekseev, M.; Amoroso, A.; Baldini Ferroli, R.; Balossino, I.; Bertani, M.; Bettoni, D.; Bianchi, F.; Chai, J.; Cibinetto, G.; Cossio, F.; De Mori, F.; Destefanis, M.; et al.
Abstract: BESIII data show a particular angular distribution for the decay of and mesons into and hyperons: the angular distribution of the decay exhibits an opposite trend with respect to the other three channels:, and . We define a model to explain the origin of this phenomenon.